Membumikan Moderasi Hukum Keluarga Islam Guna Membentuk Masyarakat Madani Menggunakan Teknologi Informasi - Wandi Sujatmiko; Irwan Adhi Prasetya; Mira Wulandari; Faqih Dzulqarnain (Pusat Riset dan Inovasi Nasional, 2024)
As society continues to develop, Information Technology is a very important tool. Information Technology forces every person, whether individual or group, private or government, to take into account the Information Technology that will be applied in order to remain competitive in the era of globalization. In general, the problem faced by the Pontianak Aisyiyah Polytechnic is that there is still a lack of knowledge in the field of law related to information technology, which has given rise to the idea of ​​establishing moderation in Islamic family law to form a civil society using information technology. Along with the progress of the development of Information Technology, globalization is becoming increasingly rapid. The specific aim is to implement the use of applications related to the theoretical concepts of the courses given to students. Analytical survey method with a Cross Sectional approach. The qualitative research design used is Phenomenological Research. The results of this research can increase students' knowledge and skills, in increasing knowledge in the field of law related to information technology. Promoting the information technology study program at the Pontianak Aisyiyah Polytechnic.